Trends, distribution and frequency analysis of ozone data from three monitoring stations in Baton Rouge, Louisiana for the years 1995 to 2005 - Klasinc, Leo (Array, 2008)
Summary: Troposphere ozone concentrations exhibit pronounced, characteristic diurnal and seasonal cycles. These cycles are usually well defined. However, additional oscillations also occur; these are generally much smaller in amplitude than the 1-day or 1-year cycles and they might be attributable to anthropogenic influences (e.g., specific man-induced meteorological and chemical influences on an individual monitoring station, periodic maintenance activities, etc.). Indeed, it is possible that the spectral analysis of photochemical pollution data could pinpoint hidden conditions that affect particular monitoring stations. Such an analysis, one based on Fourier transform methods, was applied to long-term data from 3 American monitoring stations. As would be expected, strong signals were found for the 1-day and 1-year periods; however, some weaker signals, ones probably associable with anthropogenic affairs, were also observed. A principal component analysis (PCA) was applied to the transformed data sets in order to identify these periods. Periods of 3.5-days and 7-days, as well as a number of other cycles, were found and can be considered to be markers of anthropogenic influences. European and American data will be compared and the effects of Hurricane Katrina will be examined